Dielectric environment as a factor to enhance the production yield of solvent exfoliated graphene1. Issue 79 (28th August 2015) - Srivastava, Pawan Kumar; Yadav, Premlata; Ghosh, Subhasis
<x xml:space="preserve">Abstract</x> High yield production of high quality graphene is essential for its application in electronics, optoelectronics and energy storage devices.